Cooperation models for supply chain management. Issue 1 (1st December 2008) - Marcotte, Francois; Grabot, Bernard; Affonso, Roberta
Supply chains or Supply Networks (SNs) are usually managed according to two main methods: centralised planning of the SN using an Advanced Planning System (APS), or point-to-point relationship, each partner being possibly managed by an Enterprise Resource Planning (ERP) system. The autonomy of each partner often makes the centralised planning solution questionable, whereas point-to-point relationship seems to implicitly consider that a high level plan (the Sales and Operation Planning – SOP) is generated by the final assembler, such as in the automotive or aircraft industry, and is used for building a Procurement Planning which is sent as forecasts to the partners/suppliers. Iteratively, this procurement planning should allow the suppliers building their own SOP, and then generating forecasts for their suppliers. After having performed a number of case studies in various SNs, we suggest that the characteristics of the companies involved in the SN have a deep influence on information processing, and especially on the way the procurement planning is processed. We suggest a taxonomy of collaboration situations which influence information processing all along the SN. Reference models for coordination based on this taxonomy are then presented. Typical coordination situations are discussed in order to show the practical use of these models.